“Why are These Problems Still Unresolved?” Those Pending Problems, and Neglected Contradictions in Online Classroom in the Post-COVID-19 Era - Zhao Yi; Mohd Yusof Sanitah; Hou Mingyu (Open Education Studies, 2024)
To investigate the pending problem and improve the effectiveness of online classrooms in the post-COVID-19 era, researchers conducted semi-structured interviews with 41 teachers from China, the Philippines, and other countries who have experienced long-time online classrooms. The research indicated that (1) all problems the teachers face in the online classroom can be classified into two types, including internal problems (the problems in teachers’ teaching, students’ learning, classroom discipline, and students’ psychology) and external problems (the problems in hardware and equipment, school management, education equity and privacy protection, and family interference). (2) To better improve online classroom effectiveness, teachers strongly call for a series of reforms, including the reform of school management, curriculum and teaching, after-class instruction, and psychological support, which require schools, teachers, and parents to work together to make fundamental improvements. (3) Educational equity issues caused by economic development level, long-term inefficient online interaction, and various internal contradictions are the fundamental reasons why the previous problems existing in the online classroom have not been solved. Teachers, schools, educational researchers, and government departments need to deeply study and analyze these reasons, which will help solve a series of past and present problems in the online classroom.